Free Trade with Whom? WTO, TTIP, Doha & Co - Avinash K. Dixit (ifo Schnelldienst, 2016)
– Vortrag von Prof. Avinash K. Dixit Professor Emeritus of Economics, Princeton University
Keywords: F13; F53; 330; Freihandel; Freihandelszone; WTO-Recht; TTIP-Staaten